Degradation of phenol by ultrasonic irradiation in addition of salt - Nur Ismayuslini, Saberi (2010)
Phenol is a potential hazard to human health and the environment. Sonication for phenol degradation has proved to be an attractive process over the years but percentage of phenol degradation under sonication have always been quite low and the use of catalyst also is not cost effective method. The degradation of phenol in aqueous solution was investigated by use of a 60 kHz ultrasonic reactor and all solutions volume was 100mL. Experiments were performed at initial phenol concentrations varying from 20 to 50 mg/L and different temperature in the range of 40-90oC. The pH of solution ranging from 1-4 was also adjusted by using hydrochloric acid. The effects of parameters such as initial phenol concentration, pH value, and temperature on the degradation have been studied. This research also investigated the use of simple additives such as salt on phenol degradation with an aim of cost effective method. The amount of salt used in all parameter effects was 100mg. There was comparison of phenol degradation with salt and without salt by all study effects and the phenol degradation also have been studied. The higher percentage of phenol degradation was at 20mg/L of initial concentration where the percentage of degradation was 10.2% phenol degraded without salt and 14.4% phenol degraded with salt and at pH 1 which is 28.3% phenol degraded for no salt added and 31.4% for salt added. The optimum temperature was at 70oC with 17.3% of degradation without salt and 21.3% of degradation with salt. The percentage of phenol degradation was increasing with increasing the amount of salt added. The higher percentage of degradation was 47.2% when 500mg salt was added. The results of the study showed that the ultrasonic phenol degradation increased with decreasing the pH values and initial phenol concentration and also increasing the temperature of reaction In the presence of additives, the phenol is converted into several intermediates, which are degraded faster than phenol itself so it leads to the increasing of percentage of phenol degradation.